The Australian curriculum: Continuing the national conversation. - Atweh, Bill; Singh, P. (Australian Council for Educational Research, 2011)
The purpose of this article is to identify some key areas of the Australian curriculum that remain sites of struggle and contestation. We propose that there remain a number of contentious points in relation to the national curriculum. These points relate variously to the content and form of the curricular documents; assumptions about knowledge, learning, teaching and assessment; questions about the aims and rationale of these documents; and whether the documents deal with wider economic, cultural and technological changes. These points set the scene for a continuation of the conversation about the national curriculum and provide a framework for considering the issues raised in the remaining five articles in this Special Issue on the Australian curriculum.